SGLT-2 inhibitory a jejich uplatnění v praxi - update 2022 - Prázný, Martin (Vnitrni lekarstvi, 2022)
Cardiovascular diseases are still the most common cause of mortality in patients with type 2 diabetes. Studies on the cardiovascular safety of new antidiabetic treatments, that have significantly expanded the treatment options for type 2 diabetes over the last 20 years, have provided evidence not only for the cardiovascular safety of SGLT-2 inhibitors (SGLT-2i, gliflozins), but also unexpectedly showed a significant effect on the reduction of cardiovascular risk, incidence and progress of heart failure and nephroprotectivity. For the first time, a reduction in cardiovascular and overall mortality was demonstrated for empagliflozin in 2015 in patients at very high cardiovascular risk. Further studies with gliflozins in patients with diabetes, but also in non-diabetic individuals, show that gliflozins have more pharmacological similarities than differences, especially in terms of protection against the development and progression of heart failure and maintenance of glomerular filtration rate. The revolutionary contribution of SGLT-2i is therefore perceived today not only by diabetologists, but also by cardiologists and nephrologists. In ESC guidelines, SGLT-2i are recommended as a first-line antidiabetic treatment for patients with diabetes at high cardiovascular risk, attacking the hitherto unshakable position of metformin at this pole position, and their indications should be considered in patients with type 2 diabetes with atherosclerosis, heart and renal failure regardless of the level of diabetes control (values of HbA1c). In the treatment of heart failure with reduced ejection fraction (with or without diabetes), dapagliflozin and empagliflozin have been recommended by cardiologists since 2021 to prevent hospitalizations for heart failure and to reduce mortality with the strongest class and level of evidence.
Keywords: glifloziny; clinical studies; srdeční selhání; heart failure; Hypoglycemic Agents; Diabetes Mellitus, Type 2; dyslipidemia; type 2 diabetes; SGLT2; Glycated Hemoglobin A; glykovaný hemoglobin; metformin; Benzhydryl Compounds; benzhydrylové sloučeniny; SGLT2 inhibitors; cardiovascular risk; FGF23; Metformin; Heart Failure; type 2 diabetes; Glucosides; hypoglykemika; glukosidy; diabetes mellitus 2. typu; Sodium-Glucose Transporter 2 Inhibitors; lidé; Humans; chronic kidney disease; Glycated Hemoglobin